2012
DOI: 10.1007/s00253-012-4378-4
|View full text |Cite
|
Sign up to set email alerts
|

Hydrolysis and acidification of waste-activated sludge in the presence of biosurfactant rhamnolipid: effect of pH

Abstract: In this investigation, the effect of pH (4.0-11.0) on waste-activated sludge (WAS) hydrolysis and acidification in the presence of a biosurfactant rhamnolipid (RL) were studied. The results showed that the hydrolysis and acidification of WAS in the presence of RL at alkaline pH values were more efficient than that at acidic and near-neutral pH values. After 6 h of hydrolysis, the soluble protein and carbohydrate were 1,654.7 and 675.9 mg/L (pH 11.0), and 825.6 and 376.0 mg/L (pH 7.0), whereas the values were o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(12 citation statements)
references
References 31 publications
0
12
0
Order By: Relevance
“…This may be due to biosurfactant activity of the inoculated bacteria which caused a large amount of colloidal and insoluble organic into soluble organics. Most of the bacteria found in WAS are mainly gram negative bacteria of which the external membrane is made up of lipopolysaccharides (LPS) and phospholipids covalently linked to peptidoglycan layer through hydrophobic interactions (Luo et al, 2013). Sotirova et al (2009) have reported that biosurfactant may bind to the outer membrane of the bacteria and releases the LPS thereby enhancing the solubilization efficiency.…”
Section: Ss Reduction and Cod Solubilization By Phase Separated Pretrmentioning
confidence: 99%
See 2 more Smart Citations
“…This may be due to biosurfactant activity of the inoculated bacteria which caused a large amount of colloidal and insoluble organic into soluble organics. Most of the bacteria found in WAS are mainly gram negative bacteria of which the external membrane is made up of lipopolysaccharides (LPS) and phospholipids covalently linked to peptidoglycan layer through hydrophobic interactions (Luo et al, 2013). Sotirova et al (2009) have reported that biosurfactant may bind to the outer membrane of the bacteria and releases the LPS thereby enhancing the solubilization efficiency.…”
Section: Ss Reduction and Cod Solubilization By Phase Separated Pretrmentioning
confidence: 99%
“…4a. It was expected that the deflocculating agent CaCl 2 decreases the cohesiveness of the floc matrix and the subsequent biosurfactant producing bacteria improves the solubilization by utilizing the disintegrated organic matters of the flocs thereby increasing the cell permeability and accelerating the release of significant levels of extracellular proteins and carbohydrates (Luo et al, 2013). The release profile of these soluble compounds was divided into 2 stages i.e.…”
Section: Soluble Organic Release By Phase Separated Pretreatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…The activated sludge processes produce a large amount of excess sludge, which may cause a serious of environmental and health issues. Cost of sludge treatment and disposal accounts for about half or even up to 60% of the total cost in wastewater treatment plants (WWTPs) (Luo et al, 2013). To minimize and utilize the excess sludge is becoming the most important and challenging problems in the field of wastewater treatment (Zhang et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…However, the major issue of this technology is the huge amounts of generated waste activated sludge. In China alone, about 4.6 million tons of dry sludge was produced in 2012 (Ministry of Housing and Urban-rural Development of China 2013), and the cost of sludge treatment accounts for 20-60 % of capital and operation costs of WWTPs (Luo et al 2013). Therefore, the disposal of WAS became one of the most important issues for WWTPs.…”
Section: Introductionmentioning
confidence: 99%